2015
DOI: 10.5489/cuaj.2619
|View full text |Cite
|
Sign up to set email alerts
|

Does perineural invasion in a radical prostatectomy specimen predict biochemical recurrence in men with prostate cancer?

Abstract: Introduction: The ability of perineural invasion (PNI) in radical prostatectomy (RP) specimens to predict biochemical recurrence (BCR) is unclear. This study investigates this controversial question in a large cohort. Methods: A retrospective analysis was undertaken of prospectively collected data from 1497 men who underwent RP (no neoadjuvant therapy) for clinically localized prostate cancer. The association of PNI at RP with other clinicopathological parameters was evaluated. The correlation of clinicopathol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
17
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 16 publications
(19 reference statements)
1
17
2
Order By: Relevance
“…This is likely explained by the fact that we used a strict definition of PNI, that of circumferential encirclement of nerves by malignant glands. In contrast, prior studies reporting a higher PNI prevalence either did not describe how PNI was defined (14, 19, 20, 25, 39) or used vague descriptions such as presence of tumor cells “in the perineural space” (16, 18) or “along the perineural sheath” (21). Because the perineural space can often be difficult to identify using H&E stains alone, abutment of the perineural space by both malignant and benign glands can, in the absence of circumferential involvement, be misinterpreted as PNI (53, 54), resulting in misclassification.…”
Section: Discussionmentioning
confidence: 98%
“…This is likely explained by the fact that we used a strict definition of PNI, that of circumferential encirclement of nerves by malignant glands. In contrast, prior studies reporting a higher PNI prevalence either did not describe how PNI was defined (14, 19, 20, 25, 39) or used vague descriptions such as presence of tumor cells “in the perineural space” (16, 18) or “along the perineural sheath” (21). Because the perineural space can often be difficult to identify using H&E stains alone, abutment of the perineural space by both malignant and benign glands can, in the absence of circumferential involvement, be misinterpreted as PNI (53, 54), resulting in misclassification.…”
Section: Discussionmentioning
confidence: 98%
“…Similarly, Yu [ 19 ] and Wong [ 26 ] considered that PNI is an independent risk factor associated with an increased risk of BCR in patients who undergo external beam radiotherapy. On the contrary, Reeves [ 27 ] and Freedland [ 28 ] reported that PNI is not correlated with extracapsular extension and BCR in PCa after RP. Nevertheless, Weight [ 29 ] suggested that the presence of PNI is not a significant predictor of BCR in patients undergoing brachytherapy (BT) for PCa, and Ding[ 30 ] demonstrated a significant independent association between PNI and an increased risk of biochemical failure in 185 PCa patients who received BT.…”
Section: Discussionmentioning
confidence: 99%
“…Though there are opposing views in studies investigating the correlation between PNI positivity and BR, the majority of studies state that it may be an effective factor on BR rates. In a study of 1497 patients researching this topic and producing contrary results, though PNI positivity was reported not to have an effect on BR, they stated there was a significant correlation with RRP GS, high stage, surgical margin positivity and tumor volume [22]. Another of these studies assessed 3226 patients and showed that in patients with PNI, the advanced stage disease, surgical margin positivity and BR rates were significantly higher and adding PNI to PSA, PNB GS and clinical stage provided more significant results to predict local invasion [7].…”
Section: Discussionmentioning
confidence: 97%